Family-Based Genetic Association for Molar-Incisor Hypomineralization - Jeremias, Fabiano [UNESP]; Pierri, Ricardo A.G. [UNESP]; Souza, Juliana F.; Fragelli, Camila Maria B. [UNESP]; Restrepo, Manuel [UNESP]; Finoti, Livia S. [UNESP]; Bussaneli, Diego G. [UNESP]; Cordeiro, Rita C.L. [UNESP]; Secolin, Rodrigo; Maurer-Morelli, Claudia V.; Scarel-Caminaga, Raquel M. [UNESP]; Santos-Pinto, Lourdes [UNESP] (Karger Publishers, 2016)
Despite some evidence of genetic and environmental factors on molar-incisor hypomineralization (MIH), its aetiology remains unclear. This family-based genetic association study aimed more comprehensively to investigate the genetic carriage potentially involved in MIH development. DNA was obtained from buccal cells of 391 individuals who were birth family members of 101 Brazilian nuclear families. Sixty-three single nucleotide polymorphisms (SNPs) were investigated in 21 candidate genes related to amelogenesis using the TaqMan™ OpenArray™ Genotyping platform. All SNPs were genotyped in 165 birth family members unaffected by MIH, 96 with unknown MIH status and 130 affected individuals (50.7% with severe MIH). Association analysis was performed by the transmission/disequilibrium test (TDT), and statistical results were corrected using the false discovery rate. Significant results were obtained for SNPs rs7821494 (FAM83H gene, OR = 3.7; 95% CI = 1.75-7.78), rs34367704 (AMBN gene, OR = 2.7; 95% CI = 1.16-6.58), rs3789334 (BMP2 gene, OR = 2.9; 95% CI = 1.34-6.35), rs6099486 (BMP7 gene, OR = 2.2; 95% CI = 1.14-4.38), rs762642 (BMP4 gene, OR = 2.3; 95% CI = 1.38-3.65), rs7664896 (ENAM gene, OR = 2.1; 95% CI = 1.19-3.51), rs1711399 (MMP20 gene, OR = 0.4; 95% CI = 0.20-0.72), rs1711423 (MMP20 gene, OR = 2.1; 95% CI = 1.18-3.61), rs2278163 (DLX3 gene, OR = 2.8; 95% CI = 1.26-6.41), rs6996321 (FGFR1 gene, OR = 2.7; 95% CI = 1.20-5.88), and rs5979395 (AMELX gene, OR = 11.7; 95% CI = 1.63-84.74). Through this family-based association study, we concluded that variations in genes related to amelogenesis were associated with the susceptibility to develop MIH. This result is in agreement with the multifactorial idea of the MIH aetiology, but further studies are necessary to investigate more thoroughly the factors that could influence MIH.
Keywords: Genetic association study; Genetic polymorphisms; Tooth hypomineralization